Overvalued Equities and Audit Fees: A Research Note - Habib, A.; Gong, R.; Hossain, Mahmud (Emerald Group Publishing Ltd., 2013)
Purpose – The purpose of this research note is to examine the association between overvalued equities and audit fees in the USA. Design/methodology/approach – The paper employs a standard audit fee regression model incorporating proxies for overvalued equities and controls for other known determinants of audit fees. Three proxies for overvaluation are used in this paper. These are: a lagged price-earnings-based overvaluation measure; a lagged price-to-book-based overvaluation measure; and finally, a lagged abnormal-return-based overvaluation proxy measure. Findings – Findings show that auditors charge higher audit fees for clients posing increased audit risks because of equity overvaluation, that this relationship did not change during and after the global financial crisis period, and is more pronounced for firms prone to aggressive earnings management.Practical implications – This finding should assure investors about audit quality, since the positive finding potentially implies that auditors exert extra audit effort in auditing financial statements of firms that have been identified as overvalued. This finding should also provide some evidence to audit regulators that the audit profession incorporates audit risk into audit pricing. However, since no test has been conducted to identify the association between clients' business risk and audit effort, the positive association between equity overvaluation and audit fees should be interpreted in light of this limitation. Originality/value – Jensen cautions that firms with overvalued equities suffer substantial agency costs. Although empirical research has documented managerial responses to overvaluation, there exists scant empirical evidence on auditors' response to the increased risk emanating from equity overvaluation. Since external auditors perform a significant role in ensuring the credibility of financial statements, it is important to understand whether auditors efficiently price this risk while determining audit fees.